Analysis Sociability of Visitors to Public Open Spaces in Sheikh Yusuf Gowa Field: Analisis Kemasyarakatan Pengunjung Ruang Terbuka Publik di Lapangan Syekh Yusuf Gowa - Natsir, Ni'mah (Journal of Multidisciplinary Science, 2023)
Public space is one of the vital components of urban planning. Because most buildings in urban areas in recent years, forget the existence of public space for the community, which has the opportunity to create gaps between layers of society. The purpose of this study is to examine the sociality in the field of Sheikh Yusuf in the morning and evening so as to produce an output that explains the public space is an active public space. The research method used by the author is survey method and descriptive analysis method to analyse the condition of public space in Syech Yusuf Field, Gowa. Based on the results of data analysis obtained in the field, it is known that the field of Sheikh Yusuf is used by all groups, to meet with friends or family, to carry out various activities such as sports and recreation so that it can be concluded that this field is a successful public open space based on the aspects of a friendly place according to the Project of Public Space (PPS). Keywords: Open Space, Sociability, Project of Public Space (PPS)